The functional diversity of protein lysine methylation - Sylvain Lanouette; Vanessa Mongeon; Daniel Figeys; Jean‐François Couture (Molecular Systems Biology)
Abstract Large‐scale characterization of post‐translational modifications (PTMs), such as phosphorylation, acetylation and ubiquitination, has highlighted their importance in the regulation of a myriad of signaling events. While high‐throughput technologies have tremendously helped cataloguing the proteins modified by these PTMs, the identification of lysine‐methylated proteins, a PTM involving the transfer of one, two or three methyl groups to the ε‐amine of a lysine side chain, has lagged behind. While the initial findings were focused on the methylation of histone proteins, several studies have recently identified novel non‐histone lysine‐methylated proteins. This review provides a compilation of all lysine methylation sites reported to date. We also present key examples showing the impact of lysine methylation and discuss the circuitries wired by this important PTM.